2018
DOI: 10.1371/journal.pone.0191272
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide identification of wheat and Brachypodium type one protein phosphatases and functional characterization of durum wheat TdPP1a

Abstract: Reversible phosphorylation is an essential mechanism regulating signal transduction during development and environmental stress responses. An important number of dephosphorylation events in the cell are catalyzed by type one protein phosphatases (PP1), which catalytic activity is driven by the binding of regulatory proteins that control their substrate specificity or subcellular localization. Plants harbor several PP1 isoforms accounting for large functional redundancies. While animal PP1s were reported to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Qin et al (2014) also found that TOPP4-GFP associates with the plasma membrane of root cells in Pro35S:TOPP4-GFP transgenic plants. A cytoplasmic and nuclear localization was also reported for the rice OsPP1a-GFP (Ogawa et al, 2011) and the wheat TdPP1a-GFP (Bradai et al, 2018). So far, all the identified components of the CWI pathway in PTs have been shown to be delivered to the plasma membrane (ANX1/2, BUPS1/2, RBOHH/J, and MRI) (Boisson-Dernier et al, 2009, 2013Ge et al, 2017) or to be associated with vesicles and the CW (LRX8, LRX9, and LRX10 [Wang et al, 2018] and possibly RALF4 and RALF19 [Ge et al, 2017]).…”
Section: Discussionmentioning
confidence: 66%
“…Qin et al (2014) also found that TOPP4-GFP associates with the plasma membrane of root cells in Pro35S:TOPP4-GFP transgenic plants. A cytoplasmic and nuclear localization was also reported for the rice OsPP1a-GFP (Ogawa et al, 2011) and the wheat TdPP1a-GFP (Bradai et al, 2018). So far, all the identified components of the CWI pathway in PTs have been shown to be delivered to the plasma membrane (ANX1/2, BUPS1/2, RBOHH/J, and MRI) (Boisson-Dernier et al, 2009, 2013Ge et al, 2017) or to be associated with vesicles and the CW (LRX8, LRX9, and LRX10 [Wang et al, 2018] and possibly RALF4 and RALF19 [Ge et al, 2017]).…”
Section: Discussionmentioning
confidence: 66%
“…The genomic organization within the clusters and the protein primary sequence is conserved. The presence of distinct PP1 isoforms may lead to functional distinction [27]. PP1c isoforms share 90.9–99.7% amino acid similarities indicating a high degree of functional redundancy among them [25].…”
Section: Ser/thr Phosphatasesmentioning
confidence: 99%
“…They have highly conserved Ser/Thr phosphatase domain at the N‐terminal as well as catalytic central core domain, particularly motifs involved in microcystin inhibition docking (SAPNYC), phosphate binding (VDRG and GNHE) and metal coordination (GDxHG, DxVDRG, and GNHE). Most PP1s show ETLMCSF motif for binding PIPs except for Arabidopsis TOPP4, which has ENLMCSF motif [27]. TOPP4 directly binds DELLA proteins [32].…”
Section: Ser/thr Phosphatasesmentioning
confidence: 99%
See 2 more Smart Citations